PENCATATAN PERNIKAHAN PERSPEKTIF MAQASHID SYARIAH JASSER AUDA - Budiyanto; Andika Mubarok (An Natiq, 2023)
The number of negative impacts received by husband and wife and children as a result of not registering marriages shows that having marriage registration regulations is something that is very urgent to fight for. Marriage registration rules have led to speculation that marriage registration is only considered an administrative requirement. So that until now, unregistered marriages are often found in society. The purpose of this study is to show the urgency of registering marriages for the parties involved in the marriage. The type of research used is library research originating from regulations, books, writings and others that support this research. This research is a descriptive analysis research which objectively describes the rules for registering marriages by analyzing them using the maqaṣhid sharia system theory as a methodology of Islamic legal philosophy. The author analyzes the marriage registration rules with Jasser Auda's concept of modern Islamic law which complements and updates the classical concept of Maqaṣhid Syariah. Based on the results of the study, the rules for registering marriages are a product of renewal of Islamic law in the contemporary era. Registration of marriages resulting from renewal of Islamic law as a new form of ijtihad for marriage witnesses. By registering a marriage, the civil rights of the parties concerned will be guaranteed. The logical consequence of the development of the times is also the formation of evidence that determines whether or not a marriage is valid. Jasser Auda's system theory, known as the System Approach, is the analytical knife of this research.